2019
DOI: 10.1186/s12199-019-0770-3
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss leads to reduced nutrient intake in middle-aged and older Japanese individuals

Abstract: Reductions in masticatory function as a result of tooth loss have a negative impact on nutrient intake, decreasing general health. In addition, studies have reported an association between lower socioeconomic status (SES) and both higher numbers of lost teeth and worse nutrient intake status. Nakamura et al. conducted a study to clarify the relationship between number of teeth and nutrient intake status in their paper “Having few remaining teeth is associated with a low nutrient intake and low serum albumin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Furthermore, subjective mastication difficulties, particularly when eating hard food, begin to appear when there are < 20 teeth in the mouth [ 33 , 34 ]. Tooth loss leads to reduced nutrient intake, which, in turn, may be associated with unhealthy conditions, such as being underweight or developing certain diseases [ 25 , 32 , 35 , 36 ]. Ultimately, these factors may be linked to increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, subjective mastication difficulties, particularly when eating hard food, begin to appear when there are < 20 teeth in the mouth [ 33 , 34 ]. Tooth loss leads to reduced nutrient intake, which, in turn, may be associated with unhealthy conditions, such as being underweight or developing certain diseases [ 25 , 32 , 35 , 36 ]. Ultimately, these factors may be linked to increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the number of remaining teeth among the elderly Japanese depends on the type of dental visit [44]. Furthermore, tooth loss leads to reduced nutrient intake [45]. Therefore, we have used data on the number of remaining teeth as a confounding factor in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the number of functional dental units can result in impairments in chewing or mastication (46) , resulting in eating difficulties. Tooth loss can lead to reduced nutrient intake and low serum albumin levels (47,48) . Dental caries can also lead to masticatory dysfunction with reduced food intake (49,50) .…”
Section: Prevalence Of Underweight and Associated Factorsmentioning
confidence: 99%